Optimizing small-scale aquaculture systems in the Lake Victoria Basin Uganda through analysis of profitability drivers - Syliver Byabasaija; Moses Limuwa; Ronald Semyalo (Discover Sustainability)
Abstract Small-scale aquaculture offers potential for improving livelihoods, food security, and economic growth. However, African fish farmers struggle to achieve profitability. This study investigated the financial performance of three small-scale aquaculture systems (ponds, cages, and aquaponics) in Uganda’s Lake Victoria Basin to identify variables influencing profitability. Using stratified random sampling, 169 fish farmers from Mpigi, Wakiso, and Buikwe districts were interviewed. Econometric analysis of small-scale aquaculture systems was performed using LIMDEP 9.0 software. Profitability was measured using key financial criteria such as gross margin, net farm income, and net return on investment. Furthermore, a linear regression model was used to analyse attributes influencing profitability. The analysis considered variables such as farm size, stocking density, access to extension services, and other crucial determinants. The results revealed that cage culture achieved a positive gross margin, while pond and aquaponics systems faced financial challenges due to high fixed and variable expenses, including feed, labour, and infrastructure. Farm size and fish prices have an impact on profitability. Nevertheless, high fish feed costs, predator problems, and poor technical support hinder financial performance. To improve the financial sustainability of aquaculture systems, the study recommends cost-effective feed management practices, offering financial assistance in the form of low-interest loans, extending training, and market linkages.